Phenotypic Profile And Multi-Drug Resistance Of Biofilm Producing Staphylococcus Aureus And Escherichia Coli - Eidha Ali Bin-Hameed, (Enhanced Knowledge in Sciences and Technology, 2022)
Background: Microbes attach to the surfaces and produce extracellular polymer matrix of biofilms are involved in a wide range of human infections such as urinary tract infections (UTIs) and surgical sites infections (SSIs). Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) are the most common bacteria producing biofilms causing nosocomial infections and considered to be highly antibiotics resistance and multi-resistance drugs (MDR). Objective: To detect the phenotypic prophile of biofilm formation S. aureus and E. coli and determine the susceptibility patterns of antibiotics in Mukalla city, Hadhramaut, Yemen. Material and methods: Sixty clinical isolates of S. aureus and E. coli were isolated from UTIs and SSIs samples and identified by standard bacteriological procedures, then subjected to biofilm detection by tissue culture plate (TCP) method. Disc diffusion method was used to determine the antibiotics susceptibility patterns. Findings: TCP method detected 33(55%) strong, 15(25%) moderate and 12(20%) weak/non-biofilm producers of S. aureus and E. coli. Biofilm forming S. aureus showed higher degree of resistance against the antibiotics amoxiclav 100%, ceftazidime 95.8%, cefotaxime 62.5%, cefadroxil 45.8%, ciprofloxacin 41.7% and ceftriaxone 25% with statistically significant correlation of amoxyclav and ceftazidime resistance and bacterial biofilm production (P-value